THE EFFECT OF MELATONIN ON GLYCOSYLATION OF HEMOGLOBIN IN THE BLOOD AND FUNCTIONING OF THE GLUTATHIONE SYSTEM IN THE LIVER OF ALLOXAN DIABETIC RATS - Meshchyshen, I.F.; Yaremii, I.M.; Kushnir, O.Yu. (World of Medicine and Biology, 2012)
The paper demonstrates that in alloxan diabetic rats with occult and overt diabetes, compared with the control value, took place changes the level of basal glycemia, glycosylated hemoglobin (HbА1c), - in the blood; reduced glu-tathione (G-SH), activity of glucose-6-phosphatedehydrogenase, glutathioneper-oxydase and glutathionereductase - in the liver. A 6-week injection of melatonin in a dose of 10 mg/kg to the alloxan diabetic rats was conducive to a normalization of the indices in the group of animals with occult and overt diabetes.